Anomali Iklim El Nino dan La Nina di Indonesia pada 2013-2022 - Betti Yuniasih; Wandi Nusa Harahap; Dimas Agung Satya Wardana (AGROISTA : Jurnal Agroteknologi, 2022)
Climate anomaly phenomena are increasing in frequency and duration along with the occurance of global warming phenomena. El Nino and La Nina climate anomalies have a direct impact on agriculture. This study aims to analyze the occurrence of extreme climate phenomena El Nino and La Nina in 2012-2022 in Indonesia and their impact on rainfall in South Sumatera Province which is one of the centers of oil palm plantations. The research was conducted by identifying sea surface temperature (SST) anomalies in the Pacific Ocean and classifying them into El Nino and La Nina strength levels or normal conditions. Based on the sea surface temperature anomaly, it is known that Indonesia experienced strong El Nino events in 2014-2015 and weak El Nino in 2019. El Nino causes a prolonged dry season and decreases the amount of rainfall. The La Nina phenomenon occurs in 2020-2022 with weak to moderate strength. La Nina causes a prolonged rainy season and an increase in the amount of rainfall. Normal conditions occurred in 2013, 2016, 2017 and 2018 which were marked by sst anomalies of not more than +0.5°C and -0.5 °C. During normal conditions, South Sumatra Province has an annual rainfall of 2,500 mm, rainfall is evenly distributed throughout the year, and dry months are less than 3 months that suitable for oil palm cultivation. In the last 10 years, Indonesia has experienced the El Nino and La Nina climate anomalies with increasing frequency, duration, and level of strength.